Clockwork angel - Clare, Cassandra (New York : Margaret K. McElderry Books, 2010)
When sixteen-year-old Tessa Gray crosses the ocean to find her brother, her destination is England, the time is the reign of Queen Victoria, and something terrifying is waiting for her in London's Downworld, where vampires, warlocks and other supernatural folk stalk the gas lit streets.
Keywords: Demonology -- Fiction; Fantasy fiction